Secondary flow and oxidation coking deposition of aviation fuel. (1st March 2016) - Pei, Xinyan; Hou, Lingyun
Graphical abstract: Highlights: The effect of secondary flow on deposition depends on heat transfer and sublayer. The high temperature gradient results in the large deposits. The fuel temperature and oxygen amount affect the coke deposition. The heat-transfer correlation in the S-bend tube is modified and fitted. Abstract: The effects of a complex flow and heat transfer of aviation fuel in an S-bend tube on oxidation coke deposition were both experimentally and numerically investigated. Deposition rates on the tube walls were measured by weighing for the regional analysis. Thermal oxidation deposits in the normal and high inlet temperatures were compared at a supercritical pressure of 3 MPa and the fuel outlet temperature up to 450 °C. The secondary flows at the bend have much influence on heat transfer characteristic, resulting in a sharp decline in wall temperature and deposition in the bend section. A large amount of deposits are corresponding to the high temperature gradients before and after the two bends. The high inlet fuel temperature significantly enhances the fuel temperature and oxygen consumption in the oxidization deposition reactions. The modified heat-transfer correlation in the S-bend tube was fitted at the supercritical pressure and different heat fluxes.